DESEMPENHO DE FRANGOS DE CORTE ALIMENTADOS COM DDGS NA FASE DE CRESCIMENTO (21- 35 DIAS) - BRONSTRUP, Lamayson Gabriel Schirmann; DE SOUZA, Andréia Froés Galuci Oliveira; MASS, Adriano Rasia; DE MEDEIROS , Gabriel Dias; RISSO, Natália Matos; NOGUEIRA, Lavínia Rodrigues (ANAIS DO ENIC, 2025)
-